National income : its measurement, determination, and relation to public policy - Rosen, Sam. (New York : Holt, Rinehart and winston, Inc., 1963)
This volume is not on economic growth, although questions of growth intrude persistently. Neither is it a book on monetary theory, despite a chapter on monetary policy and consideration of monetary consequences elsewhere.
Includes bibliographical references and index.
hza 30/01/2019
Loans
Keywords: Income accounts (macroeconomics)